Synthesis of Single Phase BaFe12O19 Nanoparticle by Sol-Gel Method - Dwita Suastiyanti; Bambang Soegijono; Azwar Manaf (JURNAL ILMU PENGETAHUAN DAN TEKNOLOGI (IPTEK), 2014)
Barium hexaferrite BaFe12O19 (BHF) is a great importance as permanent magnets, particularly formagnetic recording as well as in microwave devices. Barium hexaferrite also could be used as one of the basic constituent compound of multiferroic material. Multiferroic is a class of materials that yieldsimultaneous effects of ferroelectric,ferromagnetism and ferroelasticity in the same material. So BHF must be as nanoparticle and single phase to increase magnetoelectric coupling effect showing improvement multiferroic properties in material. Barium hexaferrite powders were prepared by sol gel auto combustion method. Hence the mole ratios of Ba2+/Fe3+ were varied at 1:12; 1:11.5 and 1:11 and sintering at 850oC for 10 hours for each mole ratios. To confirm the formation of single phase, it was used X-Ray Diffraction (XRD) Phillips, PW 1835 type in the 20o-100o diffraction angle using CuKα radiation. XRD results showed that sample with mole ratios of Ba2+/Fe3+ = 1:11,5 was best sample due to having single phase, 100% BHF phase be evidenced by HighScore Plus Refinement. Using Particle Size Analyzer (PSA) from Beckman Coulter type showed that sample with mole ratios of Ba2+/Fe3+ = 1:11,5 was powder in nano size, 66 nm (<100 nm). This research confirms that sol-gel method using mole ratio of Ba2+/Fe3+ = 1:11,5 and sinter temperature at 850oC for 10 hours could be used for synthesize single phase BHF in nanoparticle.